2022
DOI: 10.3390/rs14143244
|View full text |Cite
|
Sign up to set email alerts
|

A Year-Long Total Lightning Forecast over Italy with a Dynamic Lightning Scheme and WRF

Abstract: Lightning is an important threat to life and properties and its forecast is important for several applications. In this paper, we show the performance of the “dynamic lightning scheme” for next-day total strokes forecast. The predictions were compared against strokes recorded by a ground observational network for a forecast period spanning one year. Specifically, a total of 162 case studies were selected between 1 March 2020 and 28 February 2021, characterized by at least 3000 observed strokes over Italy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…(2022) and Federico et al. (2022). Table 2 summarizes the model configurations and physical parameterizations, the selection of which is based on previous studies (e.g., Gharaylou et al., 2019; Yair et al., 2010).…”
Section: Case Studies and Methodologymentioning
confidence: 96%
See 1 more Smart Citation
“…(2022) and Federico et al. (2022). Table 2 summarizes the model configurations and physical parameterizations, the selection of which is based on previous studies (e.g., Gharaylou et al., 2019; Yair et al., 2010).…”
Section: Case Studies and Methodologymentioning
confidence: 96%
“…The first 12 hr of each simulation are considered the spin-up time, which is consistent with recent similar studies conducted by Guo et al (2022) and Federico et al (2022). Table 2 summarizes the model configurations and physical parameterizations, the selection of which is based on previous studies (e.g., Gharaylou et al, 2019;Yair et al, 2010).…”
Section: The Wrf Modelmentioning
confidence: 91%
“…The total lightning, i.e., the sum of positive, negative, and intracloud lightning, is considered for comparison with observations. Federico et al [43] showed an extensive application of the Lynn et al [44] lightning scheme to the central Mediterranean area (162 cases). Among their results, a considerable sensitivity of the number of lightning strikes predicted by the scheme to the parameterised current was shown, and, for a resolution of 3 km, the configuration with a parametrised current of 0.75 × 10 −4 A was found to be the best setting.…”
Section: Lightning Forecastmentioning
confidence: 99%
“…For lightning forecast verification, we upscaled the model output from 2 km to 24 km, following the procedure discussed in [43]. In particular, we considered 12 grid cells in both horizontal directions, and we remapped both observed and predicted strokes onto this grid, verifying the results on a 24 * 24 km 2 grid.…”
Section: Forecast Verification Proceduresmentioning
confidence: 99%
See 1 more Smart Citation